Relationship between Moderate-to-Vigorous Physical Activity with Health-Related Physical Fitness Indicators among Pakistani School Adolescents: Yaali-Pak Study - Syed Muhammad Zeeshan Haider Hamdani; Zhuang Jie; Syed Ghufran Hadier; Wang Tian; Syed Danish Haider Hamdani; Shaista Shireen Danish; Syeda Urooj Fatima (The Scientific World Journal)
Background. The current study is the foremost study exploring the relationships between moderate-to-vigorous physical activity and health-related physical fitness indicators among 12–16-year-old adolescents of the South Punjab region of Pakistan. Methods. The researcher adopted the cross-sectional research design for the study. A total of 2970 participants (1477 boys and 1493 girls) aged adolescents from South Punjab, Pakistan, completed health-related physical fitness indicators measuring strength, endurance, and aerobic capacity through a hand-grip strength test, modified pull-up test, plank test, and 20-m shuttle run test, and physical activity were subjectively assessed by International Physical Activity Questionnaire Short Form (IPAQ-SF). Linear regression models were used to explore the between moderate-to-vigorous physical activity (MVPA) with health-related physical fitness indicators. Results. Positive associations were observed between hand-grip strength (p<0.001), modified pull-up (p<0.001), plank exercise (p<0.001), and 20-m shuttle run test (p<0.001), with MVPA. The gender-specific comparison also indicated a significant (p<0.001) and positive relationship. The results revealed that as MVPA increases, body composition, muscular strength, core muscular endurance, and aerobic capacity could improve in both genders. Conclusions. MVPA appears to be an effective and reliable predictor of health-related physical fitness among school adolescents.